2023
DOI: 10.1177/01461672231151791
|View full text |Cite
|
Sign up to set email alerts
|

Big Is Bad: Stereotypes About Organizational Size, Profit-Seeking, and Corporate Ethicality

Abstract: Individuals tend to hold a dim view of for-profit corporations, believing that profit-seeking comes at the expense of ethicality. In the present research, we show that this belief is not universal; rather, people associate ethicality with an organization’s size. Across nine experiments ( N = 4,796), people stereotyped large companies as less ethical than small companies. This size-ethicality stereotype emerged spontaneously (Study 1), implicitly (Study 2), and across industries (Study 3). Moreover, we find thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 82 publications
(102 reference statements)
1
7
0
Order By: Relevance
“…First, the present research complements consumer behavior literature by showing that smallness cues have positive effects and that such underlying factors as the perception of safety and perception of healthiness can explain consumers' preference for small companies' products. Thus, we extend the work demonstrating that smallness cues positively affect consumer perceptions not only on such dimensions as trust (Green & Peloza, 2014), perceptions of ethicality (Freund et al, 2023), communion (Yang & Aggarwal, 2019), sincerity (De Vries & Duque, 2018), and higher quality of low-tech products (Woolley et al, 2023) but also perception of safety and healthiness.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…First, the present research complements consumer behavior literature by showing that smallness cues have positive effects and that such underlying factors as the perception of safety and perception of healthiness can explain consumers' preference for small companies' products. Thus, we extend the work demonstrating that smallness cues positively affect consumer perceptions not only on such dimensions as trust (Green & Peloza, 2014), perceptions of ethicality (Freund et al, 2023), communion (Yang & Aggarwal, 2019), sincerity (De Vries & Duque, 2018), and higher quality of low-tech products (Woolley et al, 2023) but also perception of safety and healthiness.…”
Section: Discussionsupporting
confidence: 74%
“…We argue that additional drivers might be at play when considering company size cues' effects on consumers' judgment and decision-making in the domain of food, which to date remain overlooked. While prior literature in the area of company size cues has to a large extent addressed nonfood domains (Freund et al, 2023;Woolley et al, 2023), we argue that consumer decision-making in the domain of food may be driven by different underlying motives. Specifically, food-related decisions are linked to self-protection motives-basic physiological needs such as hunger, thirst, or healthy functioning (Baršytė et al, 2023).…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…And does it matter for how we treat these organizations as decision-makers? In the current paper, we suggest that people tend to perceive big businesses as powerful agents that are less vulnerable and less moral than small businesses, and that this organizational categorization (Freund et al, 2023) makes it seem more acceptable to lie for personal gain when interacting with a big business.…”
Section: The Pros and Cons Of Big Businessmentioning
confidence: 77%
“…Despite the mixed consequences of big businesses in society, in the public eye, there is evidence that people might dislike large corporations in a more one-sided way. Previous research suggests that people express greater intention to support small businesses than big businesses as consumers (Paharia et al 2022;Thompson & Arsel, 2004), and even stereotype big businesses as less moral (Freund et al, 2023). Moreover, in a national survey in the United States, the latest Gallup Poll found that almost everyone in the representative sample (97%) reported a positive perception of small businesses, whereas a slight majority (53%) reported a negative view of big businesses (53%) (Saad, 2022).…”
Section: The Pros and Cons Of Big Businessmentioning
confidence: 99%